DOI: 10.29007/n912
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Outcome Prediction from H&E Whole Slide Images using Machine Learning and Automatically Inferred Phenotype Profiles

Abstract: Digital pathology (DP) is a new research area which falls under the broad umbrella of health informatics. Owing to its potential for major public health impact, in recent years DP has been attracting much research attention. Nevertheless, a wide breadth of significant conceptual and technical challenges remain, few of them greater than those encountered in the field of oncology. The automatic analysis of digital pathology slides of cancerous tissues is particularly problematic due to the inherent heterogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 25 publications
2
40
0
Order By: Relevance
“…It was then possible to train CNNs directly on the compressed WSIs (18). Others reduced the dimensionality of patches using traditional dimensionality reduction techniques, such as principal component analysis, as well as CNNs pretrained on ImageNet (16, 41). Both Zhu et al (41) and Yue et al (16) subsequently used k -means clustering and found the most discriminative clusters of patches by training CNNs in a weakly supervised manner (42).…”
Section: Deep Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…It was then possible to train CNNs directly on the compressed WSIs (18). Others reduced the dimensionality of patches using traditional dimensionality reduction techniques, such as principal component analysis, as well as CNNs pretrained on ImageNet (16, 41). Both Zhu et al (41) and Yue et al (16) subsequently used k -means clustering and found the most discriminative clusters of patches by training CNNs in a weakly supervised manner (42).…”
Section: Deep Learningmentioning
confidence: 99%
“…Others reduced the dimensionality of patches using traditional dimensionality reduction techniques, such as principal component analysis, as well as CNNs pretrained on ImageNet (16, 41). Both Zhu et al (41) and Yue et al (16) subsequently used k -means clustering and found the most discriminative clusters of patches by training CNNs in a weakly supervised manner (42). However, the multi-stage structure of the aforementioned techniques does not allow processes that come first, i.e., patch compression or patch localization, to improve following the improvement of later processes, i.e., visual understanding.…”
Section: Deep Learningmentioning
confidence: 99%
“…It is no longer an exaggeration to say that computer vision is pervasive in everyday life: Face detection [1,2] has been a standard feature of digital cameras and smartphones for well over a decade, online image depositories are increasingly successful at categorizing images by their semantic content (scene: Beach, city, countryside, etc; objects: Cars, buildings, dogs, churches, statues, etc.) [3,4], automatic diagnosis and prognosis of diseases has even surpassed the performance of human experts in some domains [5][6][7], etc. This success, coupled with the increasing pervasiveness of powerful computing devices and the dramatic improvement in user-friendliness of technology in general, is having a positive impact on inter-disciplinary research, with a growing interest in the application of modern computer science in other scientific fields, as well as in the arts and humanities [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It is no longer an exaggeration to say that computer vision is pervasive in everyday life: Face detection [1,2] has been a standard feature of digital cameras and smartphones for well over a decade, online image depositories are increasingly successful at categorizing images by their semantic content (scene: Beach, city, countryside, etc; objects: Cars, buildings, dogs, churches, statues, etc.) [3][4][5], automatic diagnosis and prognosis of diseases has even surpassed the performance of human experts in some domains [6][7][8], etc. This success, coupled with the increasing pervasiveness of powerful computing devices and the dramatic improvement in user-friendliness of technology in general, is having a positive impact on inter-disciplinary research, with a growing interest in the application of modern computer science in other scientific fields, as well as in the arts and humanities [9][10][11].…”
Section: Introductionmentioning
confidence: 99%